Analisis Faktor-Faktor yang Mempengaruhi Asset Misappropriation Berdasarkan Fraud Diamond Theory: Studi Kasus pada PT. XYZ - Anggi Yunita Priyadi; Indra Cahya Kusuma; Ayi Jamaludin Aziz (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This research aims to make an analysis of the factors that influence asset misappropriation based on the Fraud Diamond Theory, with a focus on pressure, opportunity, rationalization, and capability as the main variables. Using a quantitative approach, data was collected from employees of PT XYZ through a survey-based questionnaire. This study used multiple linear regression analysis through JASP 0.14.1.0 to test the relationship between these factors and asset misappropriation. The research findings prove that 2 variables namely pressure and opportunity have a positive and significant effect on asset misuse and the other 2 variables namely rationalization and ability have no effect on asset misuse.